Streamlining Haptic Design with Micro-Collision Haptic Map Generated by Stable Diffusion - Hongyu Liu; Zhenyu Gu (Applied Sciences)
Rendering surface materials to provide realistic tactile sensations is a key focus in haptic interaction research. However, generating texture maps and designing corresponding haptic feedback often requires expert knowledge and significant effort. To simplify the workflow, we developed a micro-collision-based tactile texture dataset for several common materials and fine-tuned the VAE model of Stable Diffusion. Our approach allows designers to generate matching visual and haptic textures from natural language prompts and enables users to receive real-time, realistic haptic feedback when interacting with virtual surfaces. We evaluated our method through a haptic design task. Professional and non-haptic designers each created one haptic design using traditional tools and another using our approach. Participants then evaluated the four resulting designs. The results showed that our method produced haptic feedback comparable to that of professionals, though slightly lower in overall and consistency scores. Importantly, professional designers using our method required less time and fewer expert resources. Non-haptic designers also achieved better outcomes with our tool. Our generative method optimizes the haptic design workflow, lowering the expertise threshold and increasing efficiency. It has the potential to support broader adoption of haptic design in interactive media and enhance multisensory experiences.